Effects of a qualitative training program on some biodynamic variables of the skill of arm drag go behind to a backcast in wrestling sport - Abd El-Latif, M. S. (World Journal of Sport Sciences, 2010)
The aim of the study was to identifying the impact of qualitative trainings and some biodynamic variables and the level of performing arm drag go behined to a backcast in wrestling sport. The researcher used the experimental method using the pre and post measurements for a single group as it is suitable for this study,implementing the suggested program in improving the skill performance and biodynamic variables.